(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article is devoted to the essence of the communicative-activity approach and the algorithm of transition to a competence-based approach in teaching a foreign language, in particular Russian. The implementation of a communicative approach to teaching in Russian classes based on modern technologies naturally correlates with the problem of forming a student as a linguistic personality who owns all types of speech activity, providing the formation of listening, reading, speaking skills and abilities that are able to solve various tasks in the process of generalization.